Narcissus rupicola Dufour ex Schult. & Schult. fil. (Amaryllidaceae), novedad florística para Andalucía occidental (España) - Tirado, Javier López (Acta Botanica Malacitana, 2018)
Narcissus rupicola Dufour ex Schult. & Schult. fil. (Amaryllidaceae), new record for western Andalusia (Spain) Palabras clave. Corología, Amaryllidaceae, Narcissus rupicola, novedad, Córdoba. Key words. Chorology, Amaryllidaceae, Narcissus rupicola, new record, Cordoba.